2010
DOI: 10.1080/10510971003603960
|View full text |Cite
|
Sign up to set email alerts
|

Parental Invasive and Children's Defensive Behaviors at Home and Away at College: Mediated Communication and Privacy Boundary Management

Abstract: Following recent discussion of close parent-undergraduate contact via mediated communication, this manuscript reports an empirical study of parental invasive behaviors and children's defensive behaviors. Results reveal patterns of parent=child boundary management via mediated communication, including decreased frequency of invasive= defensive behaviors than in a similar study by Petronio (1994). Telephone invasion at home was associated with invasions when away at college. Discussion of results considers how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
(29 reference statements)
1
15
0
1
Order By: Relevance
“…Prior research has compared covert monitoring to a general dimension of overt monitoring (Cottrell et al., ), as well as to parental behaviors that overtly disrespect college students' privacy boundaries but are not necessarily geared toward information seeking (i.e., entering bedrooms without knocking, giving unsolicited advice) (Ledbetter et al, ; Ledbetter & Vik, ; Petronio, ). However, the multiple differences observed in earlier studies between overt solicitation and control also raise questions of how they each compare to covert behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has compared covert monitoring to a general dimension of overt monitoring (Cottrell et al., ), as well as to parental behaviors that overtly disrespect college students' privacy boundaries but are not necessarily geared toward information seeking (i.e., entering bedrooms without knocking, giving unsolicited advice) (Ledbetter et al, ; Ledbetter & Vik, ; Petronio, ). However, the multiple differences observed in earlier studies between overt solicitation and control also raise questions of how they each compare to covert behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that, although youths might find overt demands for information to be intrusive, they can potentially mitigate this association through a combination of disclosures, omissions, and outright refusals (Hawk et al., , ; Marshall et al., ; Petronio, ). In contrast, the unpredictability and covert nature of snooping negates youths' agency in choosing responses that best suit their privacy needs (Ledbetter et al, ; Ledbetter & Vik, ; Petronio, , ).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are a number of investigations into issues surrounding Facebook usage (e.g., Waters & Ackerman, 2011), exploring the sense of publicness in social networks (Bateman, Pike, & Butler, 2011), and online dating (e.g., Gibbs, Ellison, & Lai, 2011). Further, there have been investigations into parental behavior that is enacted through online social media (e.g., Ledbetter, Heiss, Sibal, Lev, Battle-Fisher, & Shubert, 2010).…”
Section: Online Social Media and Cpmmentioning
confidence: 99%
“…However, parents who engage in controlling and intrusive behaviors disrupt their emerging adults' ability to separate from the family and establish individual identities and autonomy (Kins et al, 2011(Kins et al, , 2013. Parents may exert control over their children even at a distance (Ledbetter et al, 2010). Children often report lower satisfaction with the parent-child relationship and more frequent conflict with parents tied to parental privacy invasions (Hawk, Keijsers, Hale, & Meeus, 2009;Petronio, 1994).…”
Section: Connection-autonomy Issues In Emerging Adulthoodmentioning
confidence: 99%